AESTHETICS OF ART IN THE PRACTICE OF MAKEUP AND TRADITIONAL WEDDING CLOTHING IN SURAKARTA (Pena Cendekia Insani, 2026)
Aesthetic inquiry in art extends beyond purely sensory notions of beauty to encompass layers of meaning shaped by cultural constructions. This study aims to examine the aesthetics embedded in the practice of bridal makeup and attire in Surakarta traditional weddings, with particular emphasis on the interrelationship between visual form, symbolic meaning, and cultural values. The research adopts a qualitative approach employing a descriptive-interpretative method grounded in a systematic literature review. The data sources comprise primary data in the form of visual documentation of Surakarta bridal makeup and attire, alongside secondary data drawn from scholarly books, peer-reviewed journal articles, and relevant prior studies. Data collection was conducted through documentation analysis and comprehensive literature review, guided by inclusion criteria focusing on thematic relevance, academic credibility, and recency of publication. Data analysis was carried out through stages of data reduction, thematic categorization, symbolic interpretation, and conclusion drawing, utilizing a hermeneutic framework to uncover deeper layers of meaning. The findings reveal that the aesthetics of Surakarta bridal makeup particularly in the Solo Putri and Solo Basahan paes styles transcend visual ornamentation and function as a symbolic system representing philosophical values such as self-restraint, purity, and existential harmony. Furthermore, bridal attire, as expressed through batik motifs and chromatic composition, embodies cultural aspirations toward a balanced and prosperous marital life. This study demonstrates that aesthetics operates not merely as a visual attribute but as a complex medium of cultural and spiritual communication. Its contribution lies in advancing the discourse on art aesthetics within the context of local cultural practices and in offering critical insights into the preservation of intangible cultural heritage through a deeper understanding of symbolic meanings.